KERJA SAMA INDONESIA, MALAYSIA, THAILAND-GROWTH TRIANGLE (IMT-GT) DALAM MENINGKATKAN PENANAMAN MODAL ASING PROVINSI JAMBI TAHUN 2017-2021 - Feby Rachma Alfi Dhiandra (2023)
Border areas tend to have unequal economic development compared to the capital cities. To catch up with the capital cities, border areas like Jambi Province needs to seek economic advancement by using other ways, one of them being through international cooperation. Jambi Province has promising economic potential but needs support with the help of Foreign Direct Investment (FDI). The purpose of this study is to look at the dynamics of cooperation that occurs between the Indonesia Malaysia Thailand-Growth Triangle (IMT-GT) which participated by Jambi Province in 2017-2021. The method used in this study is a descriptive analysis method which will describe research problems based on data in narrative form. Secondary data were used through literature studies. The result of the study indicated that IMT-GT is an economic forum in that Jambi Province is participating in, IMT-GT has a role as an Investment facilitator, IMT-GT's goal is to connect Jambi Province with the potential investors and provide a promotional platform. However, in the IMT-GT framework for 2017-2021, many obstacles were found, such as Thailand's inability to invest in Jambi Province for economic reasons, the Covid-19 pandemic that affects the global economy, and others.